ASSESSMENT OF THE IMPACT OF MOTIVATIONAL FACTORS ON WORK EFFICIENCY AND ORGANIZATIONAL BEHAVIOR - Janošik, Marija; Živadinović, Bojan; Doljanica, Suzana; Milikić, Natalija; Gavrilović, Milan; Jovanović, Dražen (ACADEMIC REVIEW, 2025)
Comprehending employee motivation is crucial for enhancing job performance and organizational conduct in the contemporary, rapid business environment This study investigates the impact of intrinsic and extrinsic motivation on employee performance and interactions, given their influence on employment outcomes. Acknowledgment, accolades, and opportunity for personal development enhance productivity and organizational culture. This study contrasts intrinsic motivations, such as personal satisfaction and career advancement, with extrinsic rewards, including bonuses and promotions, to assess their impact on job efficiency. Furthermore, employee recognition can enhance motivation and productivity, influencing business culture and conduct. The project will investigate how these motivational factors might be intentionally utilized to enhance employee collaboration and teamwork, fostering a supportive work environment. This research will elucidate how businesses can apply motivational tactics to enhance employee performance and foster a cohesive organizational culture, addressing the critical inquiry of how motivation influences job efficacy and organizational behavior.